Etnogênese Quilombola e Indígena no Território Agreste-Litoral Sul na Implementação do Projeto RN Sustentável: um Olhar Sobre a Relação (ou da Ausência desta) Entre Antropologia Versus Desenvolvimento - Oliveira Junior, Geraldo Barboza de (Trabalhos de Antropologia e Etnologia, 2020)
This article aims to address the construction of a new scenario in public policies for social development in the State of Rio Grande do Norte: the inclusion of specific traditional communities (quilombolas and indigenous) as target audience of these policies; and at the same time, we show how the phenomenon known as ethnogenesis (construction of an ethnic identity) emerges, still very expressive way, in order to give visibility to these groups and make them able to achieve success in social policies. In particular, the eye falls on an experience like territorial articulator in Sustainable RN Project in Agreste Territory / South Coast, in the period of 12 months, with groups of farmers and indigenous and quilombo communities. As a result, it was realized that the lack of confidence of the traditional communities in public policy resulted in a shy little participation or purposive social actors of these communities in expressions of interest in participating in the three calls proposed in that project. Finally, we believe that the absence of an anthropological sense in building a sustainable development project (together with other factors) involving traditional communities contributed to his little success in traditional maroon and indigenous communities in this project in its initial phase.